The future of lupin as a protein crop in Europe - Lucas, M. Mercedes; Stoddard, Frederick L.; Annicchiarico, Paolo; Frias, Juana; Martinez-Villaluenga, Cristina; Sussmann, Daniela; Duranti, Marcello; Seger, Alice; Zander, Peter M.; Pueyo, José J. (Frontiers in Plant Science, 2015)
Europe has become heavily dependent on soya bean imports, entailing trade agreements and quality standards that do not satisfy the European citizen’s expectations. White, yellow and narrow-leafed lupins are native European legumes that can become true alternatives to soya bean, given their elevated and high-quality protein content, potential health benefits, suitability for sustainable production, and acceptability to consumers. Nevertheless, lupin cultivation in Europe remains largely insufficient to guarantee a steady supply to the food industry, which in turn must innovate to produce attractive lupin-based protein-rich foods. Here, we address different aspects of the food supply chain that should be considered for lupin exploitation as a high-value protein source. Advanced breeding techniques are needed to provide new lupin varieties for socio-economically and environmentally sustainable cultivation. Novel processes should be optimized to obtain high-quality, safe lupin protein ingredients, and marketable foods need to be developed and offered to consumers. With such an integrated strategy, lupins can be established as an alternative protein crop, capable of promoting socio-economic growth and environmental benefits in Europe.